The oxygen saturation of red blood cell concentrates: The basis for a novel index of red cell oxidative stress. Issue 1 (10th November 2021) - Yoshida, Tatsuro; McMahon, Emma; Croxon, Harry; Dunham, Andrew; Gaccione, Peter; Abbasi, Babak; Beckman, Neil; Omert, Laurel; Field, Stephen; Waters, Allison
Abstract: Background: Oxidative stress is a major driving force in the development of storage lesions in red cell concentrates (RCCs). Unlike manufactured pharmaceuticals, differences in component preparation methods and genetic/physiological status of donors result in nonuniform biochemical characteristics of RCCs. Various characteristics of donated blood on oxygen saturation (SO2 ) distribution were investigated, and a model to estimate potential oxidative stress burden of stored RCC at transfusion is proposed. Study design and methods: The oxygen content of freshly prepared RCCs (770) was quantified noninvasively as fractional hemoglobin saturation (SO2 ) with visible reflectance spectrometry. Using separate RCCs and mimicking typical handling of RCCs during routine storage, evolution of SO2 was followed for construction of an empirical model. Based on this model, the oxygen exposure index (OEI) was formulated to estimate the accumulated oxygen exposure burden of RCC at the time of transfusion. Results: The SO2 of RCCs varied widely at donation (mean 43% ± 1.3%; range 20%–93%). Multivariate regression model showed that sex and processing method had small effects on SO2 ( R 2 = 0.12), indicating that variability was mainly attributed to other individual donor characteristics. Storage simulation model indicated that median SO2 increased gradually over 6 weeks (approx. 1.3 fold), while OEI increased at a faster rate (approx. eight‐fold). Conclusion: In addition to storage age, the OEI provides a potential new metric to assess the quality of RCCs at the time of transfusion in terms of their oxidative stress. In future studies, a single noninvasive measurement during storage could link OEI to clinical outcomes in transfusion recipients.